Efektivitas Pendidikan Kesehatan Dengan Penerapan The Health Belief Model Terhadap Pengetahuan Keluarga Tentang Diare - Hudrizal Mubaroq Riauwi; Yesi - Hasneli; Widia - Lestari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2014)
Thepurposeoftheresearchwas toidentifiedtheefectivity of health education with the application of the health belief model to family knowledge about diarrhea.Theresearchusedquasy experiment designwith two group design that dividedintoexperimental andcontrolgroup.Samples of this research were 30 people that divided into experiment and control group. Samples taken by using purposive sampling techniques which selected based on inclusion criteria. Data collection’s tool in this research was a knowledge questionnaire with the method of the health belief model. The experimentalgroupweregiveninterventionswiththe health education with the application of the health belief model.Dataanalyzedwithunivariate and bivariate, using dependentsamplettest and independent samplet test. Theresult of the researchshowedthatmeanlevelofknowledge before intervention was 21,00, and after was 25,20 (p value 0,009). It means there is an increasing knowledge about diarrhea of the family and health education with application of health believe models could increasing family’s knowledge. The resultofthis research recommend that health education with application of health believe model could be part of nursing intervention to increase family’s knowledge about diarrhea. Keywords : Diarrhea, health belief model,knowledge,